Electoral coalition signals and voter perceptions. (June 2022) - Jang, Jinhyuk; Crabtree, Charles; Golder, Sona N.
Abstract: How do electoral coalition signals affect voters' perceptions of party positions and coalition behavior in parliamentary democracies? Scholars have found that coalition signals can influence how voters view policy positions of parties. Extending research on the impact of government coalition participation on voter perceptions, a recent study found that Spanish voters update their perceptions of party positions when they receive a signal that a party joined an electoral coalition, believing it to be farther to the left (right) if the signal was of a left- (right-)leaning coalition. That study also found, in agreement with the literature, that electoral coalition signals lead to expectations of future coalition behavior. Much of the literature on electoral coalitions focuses on parliamentary democracies in Europe that use proportional representation. Since the effects of electoral coalitions might vary across contexts, we conduct a similar survey experiment in Japan, a parliamentary democracy that uses a mixed electoral system with an important disproportional component. We find no evidence that electoral coalition signals affect how Japanese voters view the ideological positions of parties, a result that matches a similar analysis conducted in Sweden. However, some coalition signals – if they contain new information – do increase Japanese respondents' expectations that certain coalitions are more likely to form in the future.